Analysis of TheVadility of A Cession Over A Receivables Sale and Purchase Agreement That Was Subject to an Invalid Novation - Bella Fabiola; Akhmad Budi Cahyono (Faculty of Law, Universitas Pekalongan, 2022)
In order to guarantee smooth capital turnover, banks would often